Chemical & Mineralogical Properties of Fly Ash - Khairul Nizar, Ismail; Kamarudin, Hussin; Mohd Sobri, Idris (Malaysian Nuclear Society, 2009)
Link to publisher's homepage at http://www.nuklearmalaysia.org/